Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Toko H. Irin Kalianda - Arlinda, Ayu; Saodin, Saodin (CV. ITTC INDONESIA, 2024)
Marketing Strategy is a company guide in the form of a plan prepared systematically and comprehensively in carrying out marketing activities to achieve company goals, namely generating profits. The purpose of this research is to determine the significant influence of product on sales, price on sales, place on sales, promotion on sales and Product, Price, Place and Promotion simultaneously on sales. This research method uses a descriptive method with a quantitative approach. Instrument testing uses the t test and F test. Based on the results of partial calculations that: Product has a significant effect on sales, price has a significant effect on sales, place has a significant effect on sales and promotion has a significant effect on sales. Based on the results of simultaneous calculations, the variables Product (X1), Price (X2), Place (X3) and Promotion (X4) simultaneously have a significant effect on sales.